A large-scale benchmark for the CFD modeling of non-catalytic reforming of natural gas based on the Freiberg test plant HP POX. (15th July 2015) - Richter, Andreas; Seifert, Peter; Compart, Fred; Tischer, Paul; Meyer, Bernd
Graphical Abstract: Highlights: Natural gas reforming at high pressures and temperatures was studied experimentally. A semi-industrial test plant with comprehensive instrumentation was used. A new optical system allows the flame zone to be studied directly. Measurements were carried out at different pressures and temperatures. The data set provides a challenging benchmark for numerical modeling. Abstract: The non-catalytic reforming of natural gas to syngas was studied with test runs at the semi-industrial scale test plant HP POX. The product gas composition, and gas and wall temperatures across the reactor were considered at 50, 60 and 70 bar(g), while the reactor temperature was varied between 1200 and 1400 °C. In addition, the flame structure was studied using optical measurements. The experiment was designed to provide a challenging benchmark for numerical modeling. For that reason, the reactor geometry, boundary conditions, and the experimental data are provided in such a way that the results can easily be reproduced using CFD.